Penerapan Strategi Pembelajaran Berdiferensiasi Sebagai Bentuk Pemenuhan Kebutuhan Belajar Peserta Didik - Asti Widiastuti; Melia Nurkhalisa; Muthia Aprianti; Prihantini Prihantini (LPPM Politeknik Pratama, 2024)
A concept of freedom or independence that is applied in an educational environment can be designed in a form of learning which is commonly known as differentiated learning. Differentiated learning is a strategy in the ongoing and implementation of the independent curriculum program. This differentiated learning will run because so far the learning process that has been implemented is one-way learning that is only centered on the teacher. Therefore, this research was carried out using library research methods. Library research is a research activity carried out by collecting information and data with the help of various kinds of materials in the library.